STRATEGI PEMENANGAN PASANGAN CALON BUPATI DIAN RACHMAT YANUAR DAN TUTI ANDRIANI DALAM PEMILIHAN KEPALA DAERAH KABUPATEN KUNINGAN - Hendri Suwarsono; Rima Ismatul Muhibbah; Khalda Nur Fajria; Nadya Salsabilla Stephanie; Diva Dwi Azahra; Elsa Selvia; Adinda Salwa Salsabila (Jurnal Dialektika Politik, 2025)
The winning strategy for Regent candidate pair Dian Rachmat Yanuar and Tuti Andriani in the Kuningan Regency Regional Head Election (Pilkada) includes various political approaches designed to win voter support. This research aims to analyze the political marketing strategies used by these candidate pairs to obtain a majority of votes. This research uses a qualitative method with a descriptive approach. Data was collected through in-depth interviews with the campaign team, direct observation of campaign activities, and documentation studies related to the candidate pairs' work programs. This research also uses inductive analysis to understand the patterns and effectiveness of the strategies implemented. The research results show that the DIRAHMATI couple uses segmentation, targeting and positioning strategies to reach various voter groups. Apart from that, political communication strategies, both through social media and face-to-face activities, play a big role in building a positive image and introducing candidate pairs to the public. This victory was also driven by their ability to manage local political dynamics, including collaboration with community leaders and gathering support from political parties that have strong influence in the area.